Metode Iterasi Prediktor Korektor Jarratt Householder Untuk Penentuan Akar Persamaan Non Linier - Yoga Aprila; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2023)
Determining roots of non-linear equation are often problem in mathematics and engineering. In general, these non-linear equations will appear in complex form that make difficult to solve analytically, so assistance of numerical methods is needed to determining the roots. One of the numerical methods that can be used including Newton-Raphson’s Method, Jarratt’s Method, and Householder’s Method. However, the drawback of these methods are their low order of convergence. Predictor Corrector Jarratt-Householder Iterative Method is a method that arises due to the shortcomings of these methods. The purpose of this research is to study how the process of construction of Predictor Corrector Jarratt-Householder Iterative Method , making algorithm, and finding the order of convergence. The numerical simulation test results with several functions show that Predictor Corrector Jarratt-Householder Iterative Method can finds roots faster than Newton-Raphson’s Method, Jarratt's Method, and Householder's Method.